2006
DOI: 10.1007/s10620-006-9475-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Specific Cyclooxygenase-Gene Polymorphism (A-842G/C50T) on the Occurrence of Peptic Ulcer Hemorrhage

Abstract: Cyclooxygenases (COX) catalyze the conversion of arachidonic acid to prostaglandins (PGs). COX-inhibiting drugs, such as nonsteroidal anti-inflammatory drugs (NSAIDs), increase the risk for peptic ulcer disease. As a corollary, COX gene polymorphisms could be important in the pathogenesis of peptic ulcer disease because these affect prostaglandin formation and impair its protective effect at the level of the gastric mucosa. This study was designed to investigate the association between the functional single-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 15 publications
3
31
0
2
Order By: Relevance
“…Only a few studies have examined the physiologic consequences of genetic variation in COX-1. The previous data on genetic diversity of COX-1 in Western populations showed an inverse association between the prevalence of A-842G/C50T polymorphism and bleeding peptic ulcer disease, but the data lacked statistical significance [21]. In contrast, a recent Japanese study indicated an association of T-1676C polypmorphism with NSAID-induced ulcer [24].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Only a few studies have examined the physiologic consequences of genetic variation in COX-1. The previous data on genetic diversity of COX-1 in Western populations showed an inverse association between the prevalence of A-842G/C50T polymorphism and bleeding peptic ulcer disease, but the data lacked statistical significance [21]. In contrast, a recent Japanese study indicated an association of T-1676C polypmorphism with NSAID-induced ulcer [24].…”
Section: Discussionmentioning
confidence: 88%
“…For polymorphism of UGT 1A6, CYP2C9, TNF-a, and COX-1 PCR reactions were carried out separately using the primers described in Table 1 for multiplex amplification. PCR-restriction fragment length polymorphism (RFLP) was performed as described previously [20][21][22].…”
Section: Genotypingmentioning
confidence: 99%
“…On the other hand, although the T-1676C promoter polymorphism did not affect the two Sp1 binding sites that were reported to be essential for COX-1 transcription (14), putative transcription factor (GATA-1, CdxA) binding sites were altered by this polymorphism (15). The relationship between the A-842G/C50T polymorphism and human disorders was investigated in several reports (8,(16)(17)(18), whereas only a few studies have researched the association of the T-1676C polymorphism with human diseases. Shi et al reported that the COX-1 polymorphisms including the T-1676C polymorphism do not appear to play a substantial role in genetic predisposition for asthma or asthma severity (9).…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggests that the -842G carrier has a higher risk of developing NSAID-induced ulcer. Although Oijen et al reported that the COX-1 A-842G/C50T polymorphism did not influence the risk for developing peptic ulcer bleeding (8), the role of this polymorphism on the development of peptic ulcers still remains unclear. In addition, Shi et al have investigated the association of 4 of 20 known informative and potentially functional polymorphisms in the COX-1 gene with asthma (9).…”
Section: Introductionmentioning
confidence: 99%
“…31,32 The previous data show an inverse association between the prevalence of A-842G/C50T polymorphism and bleeding peptic ulcer disease, but lack statistical significance. 33 In contrast, a recent Japanese study indicated a possible association of COX-1 T-1676C polymorphism with NSAID-induced peptic ulcer. 34 However, there are no data supporting a significant association among aspirin users.…”
Section: Genetic Polymorphisms and Aspirin-induced Peptic Ulcer Coxmentioning
confidence: 92%